Hybrid Data Visualization Based on Depth Complexity Histogram Analysis. (5th September 2014) - Lindholm, S.; Falk, M.; Sundén, E.; Bock, A.; Ynnerman, A.; Ropinski, T.
<x xml:space="preserve">Abstract</x> We present an A‐buffer based algorithm that achieves performance gains of up to eight times relative existing techniques. The algorithm contains two novel components which improve the utilization of the local cache memory on the GPU. This is particularly important for scenes with non‐uniform depth complexities and rapidly decreasing depth complexity histograms (DCHs). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>